Determinants of sexual health information-seeking on social media among Chinese college students: an application of the Comprehensive Model of Information Seeking - Zhuowen Feng; Wei He; Jiaru Xie; Guancheng Wang; Wanfang Lin (Frontiers in Public Health, 2026)
Background Chinese college students often use social media to access sexual health information in a context of uneven formal sex education and cultural sensitivity surrounding sexuality. Understanding the factors associated with this behavior can inform sexual health communication and education. Methods A cross-sectional online survey was conducted with 283 Chinese college students. Structural equation modeling was used to examine the associations among perceived direct or vicarious experience with sexual health issues, risk-oriented salience, beliefs, perceived information carrier characteristics, perceived utility of sexual health information (SHI), and sexual health information-seeking behavior (SHISB). Results Perceived direct or vicarious experience, risk-oriented salience, beliefs, and perceived information carrier characteristics were positively associated with the perceived utility of social media for SHI. Perceived information carrier characteristics and perceived utility of SHI were positively associated with SHISB. Perceived utility served as an indirect statistical pathway linking perceived information carrier characteristics and SHISB. Conclusion The findings suggest that the Comprehensive Model of Information Seeking (CMIS) provides a useful but bounded framework for examining individual-cognitive and information-evaluation factors related to SHISB among Chinese college students. Improving the credibility, clarity, accessibility, and relevance of online sexual health information may better support students' sexual health information needs. Given the cross-sectional design and risk-oriented measurement, the findings should be interpreted as statistical associations rather than causal effects or a comprehensive account of sexual health practices.